Dari Surau ke Lapau: Pergeseran Nilai dan Perilaku Palapau Masyarakat Minang Kabau dalam Perspektif Ekonomi Islam - Yogi Saputra; Rizal Fahlefi; Ahmad Lutfi; Azifa Hidayati; Fandi Ahmad Marlion (Universitas Islam Negeri Sumatera Utara, 2025)
This research aims to analyze the shift in values and behavior of the Minangkabau community from an Islamic economic perspective using a Systematic Literature Review (SLR) approach. This study was carried out by searching 312 documents through seven academic databases, then selecting them using the PRISMA protocol to produce 31 relevant literature which was analyzed thematically. The research results show that pelapau, namely individuals who were active in lapau in the past, played a role as social actors who upheld the values of ta'awun (mutual help), qana'ah (simplicity), and amanah (responsibility) in the economic and social life of society. However, modernization and the development of consumer lifestyles have shifted the meaning of lapau from a space of valuable social interaction to an arena of entertainment and consumption, so that lapau behavior tends to deviate from the principles of maqasid al-syariah, especially in the aspects of hifz al-mal (protecting wealth) and hifz al-waqt (keeping time). This study emphasizes that the revitalization of Islamic values in pelapau behavior is necessary to restore lapau as a center for community-based social, moral and sharia economic interaction, so as to be able to re-strengthen the role of local Minangkabau culture in supporting just and ethical Islamic economic development